Biomedical Waste Management Practices of Doctors: An Online Snapshot - Mohapatra Archisman; Manoj K Gupta; Siddharudha Shivalli; CP Mishra; SC Mohapatra (Medsci Publications, 2012)
Objective: This study was undertaken with the objective to assess the professional behavior of doctors in India regarding Bio-Medical Waste (BMW) management. Methods: A predesigned questionnaire containing a set of nine open-ended questions was sent to 557 email contacts obtained randomly from social networking sites by using respondent-driven sampling technique. Non-duplicated opinions from only those respondents who had completed their medical education in India and working in the country were included for analyses. Results: Remnant knowledge of BMW management as self-adjudged was significantly (p<0.001) poor among post-graduates (35.5%) than medical graduates (75%). It was evident that proper practice of BMW segregation at the work place had a significant association (p<0.001) with higher knowledge of the same. Almost one third respondents did not know about the bio-hazardous waste symbol. Discussion and Conclusions: This study underscores the need for effective BMW management training of medicos with regular refresher sessions.